Body Mass Index’s Role in Determining Maximum Mouth Opening Using the Three-Finger Index in People of Aligarh city, Uttar Pradesh - Pradhuman Verma; Kanika Gupta Verma; Abhinaba Das; Mohammed Najmuddin; Naseebia Khan; Muzammil Moin Ahmed (Journal of Indian Academy of Oral Medicine and Radiology)
Background: Mouth opening is significant for diagnosing many clinical conditions. Therefore, it becomes essential to establish normal maximum mouth opening (MMO). Aim: To study role of BMI while evaluating MMO using three-finger index. Materials and Method: A total of 500 subjects between 20 and 60 years were considered. Thorough clinical examination was done. Subjects satisfying inclusion criteria, height (H) and weight (W) were recorded, and BMI was calculated as W/H2. Group I included under-weight (18.5 and less) subjects, Group II: normal (18.5 to 24.9), Group III: over-weight (25–29.9), and Group IV: subjects with obesity (≥30), based on BMI. Inter-incisal MMO and combined three-finger (index, middle and ring finger) width of both hands were also measured for each subject. To avoid bias, measurements were taken twice by same observer and mean was considered. Result: Maximum subjects were found in Group II and minimum in Group I. MMO was noted highest in Group III with significantly higher values in males. Both hand fingers’ width was noted maximum in Group IV again with significantly higher values among males. Statistically significant correlation (P < 0.05) was found between three-finger width and MMO in all groups. Conclusion: BMI while measuring three-finger width of hands was found to be significantly correlated with MMO in Aligarh population and may be a significant indicator of MMO.